Exacerbated climate risks induced by precipitation extremes in the Yangtze River basin under warming scenarios - Sun, Shao; Zhao, Yanxia; He, Yan; Xia, Zhihong; Chen, Sining; Zhang, Yi; Sun, Qing (Frontiers in Ecology and Evolution, 2023)
The Yangtze River basin is one of the most typical regions around the world with well-developed economy but deeply affected by multiple climate extremes. An improved understanding of future climate trends and associated exposures of this region is urgent needed to address socioeconomic risks. In this paper, historical observations and future projected population exposure to precipitation extremes in the Yangtze basin are quantified based on meteorological records and downscaled climate models. The results show that the hazard zone of precipitation extremes in baseline period is located in the mid-lower Yangtze basin, particularly around Poyang Lake watershed. Climate projections for around 2050 indicate a further increase in the occurrence of precipitation extremes in the hazard zone, while a decrease in extreme events is detectable in the upper Yangtze basin when radiative forcing raises. Future socioeconomic scenarios reveal a tendency of mass population gathering towards the lower Yangtze basin, resulting in aggravated climate risks in megacities. Multi-model simulations show that population exposure to precipitation extremes in the lower Yangtze basin will increase by 9-22% around 2050, with both climate and population factors contributing positively. Shanghai, Changsha, Hangzhou, Ganzhou, and Huanggang are identified as hotspot cities facing the highest foreseeable risks of precipitation extremes in the Yangtze basin.